Allosteric modulation of peroxisomal membrane protein recognition by farnesylation of the peroxisomal import receptor PEX19 - Leonidas Emmanouilidis (Nature Portfolio, 2017)
PEX19 is a chaperone and import receptor for peroxisomal membrane proteins (PMPs). Here the authors present the structure of the farnesylated C-terminal domain of PEX19, and its interaction with PMPs reveals how the farnesyl moiety allosterically reshapes the PMP binding surface and modulates PEX19 function.